Surgical management of ovarian tumors without the support of intraoperative pathology readings in Bhaktapur Cancer Hospital - Michelle Marinone; Eliza Shrestha; Anita Thapa; Ruhee Tuladar; Dorothy B. Wakefield; Linus Chuang (Elsevier, 2020)
Intraoperative frozen section plays an important role in surgical management of ovarian masses. Many hospitals in low- and middle-income countries lack this intraoperative pathologic guidance. In this retrospective analysis, we assessed the management of 62 patients who underwent surgical treatment for ovarian masses at Bhaktapur Cancer Hospital in Nepal in light of the final histopathology results. Final histopathology found that 64.5% of the ovarian masses were malignant, 1.0% were borderline, and 30.6% were benign. 55 of the 62 total cases were considered "clinically suspicious" and 52 of the 62 cases underwent hysterectomy and staging procedures in addition to oophorectomy. There was no significant difference in the surgical management or in the postoperative complications when comparing benign, borderline, and malignant masses. Without the support of intraoperative frozen section, benign and malignant masses were treated the same way. The majority of benign cases were overtreated and were exposed to additional risks of postoperative complications. Several malignant cases were undertreated and required additional surgery to appropriately treat and stage malignant ovarian masses. Improved pathology support in Bhaktapur Cancer Hospital would result in better patient outcomes, fewer complications, and avoidance of additional staging surgeries.